Structural comparison of allophycocyanin variants reveals the molecular basis for their spectral differences - Christopher J. Gisriel; Eduard Elias; Gaozhong Shen; Nathan T. Soulier; Gary W. Brudvig; Roberta Croce; Donald A. Bryant (Photosynthesis Research, 2024)
Allophycocyanins are phycobiliproteins that absorb red light and transfer the energy to the reaction centers of oxygenic photosynthesis in cyanobacteria and red algae. Recently, it was shown that some allophycocyanins absorb far-red light and that one subset of these allophycocyanins, comprising subunits from the ApcD4 and ApcB3 subfamilies (FRL-AP), form helical nanotubes. The lowest energy absorbance maximum of the oligomeric ApcD4-ApcB3 complexes occurs at 709 nm, which is unlike allophycocyanin (AP; ApcA-ApcB) and allophycocyanin B (AP-B; ApcD-ApcB) trimers that absorb maximally at ~ 650 nm and ~ 670 nm, respectively. The molecular bases of the different spectra of AP variants are presently unclear. To address this, we structurally compared FRL-AP with AP and AP-B, performed spectroscopic analyses on FRL-AP, and leveraged computational approaches. We show that among AP variants, the α-subunit constrains pyrrole ring A of its phycocyanobilin chromophore to different extents, and the coplanarity of ring A with rings B and C sets a baseline for the absorbance maximum of the chromophore. Upon oligomerization, the α-chromophores of all AP variants exhibit a red shift of the absorbance maximum of ~ 25 to 30 nm and band narrowing. We exclude excitonic coupling in FRL-AP as the basis for this red shift and extend the results to discuss AP and AP-B. Instead, we attribute these spectral changes to a conformational alteration of pyrrole ring D, which becomes more coplanar with rings B and C upon oligomerization. This study expands the molecular understanding of light-harvesting attributes of phycobiliproteins and will aid in designing phycobiliproteins for biotechnological applications.

Is charge recombination at the origin of Photosystem II photoinhibition? - Félix Vega de Luna; Maximiliaan Stada; Annamarie Zeekant; Thomas J. Oliver; Roberta Croce; Wojciech J. Nawrocki (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

The location of the low-energy states in Lhca1 favors excitation energy transfer to the core in the plant PSI-LHCI supercomplex - Vladimir I. Novoderezhkin; Roberta Croce (Photosynthesis Research, 2023)

The photosynthetic apparatus of the CAM plant Tillandsia flabellate and its response to water deficit - Chen Hu; Vincenzo Mascoli; Eduard Elias; Roberta Croce (Journal of Plant Physiology, 2023)

PSII supercomplex disassembly is not needed for the induction of energy quenching (qE) - Ludwik W. Bielczynski; Pengqi Xu; Roberta Croce (Photosynthesis Research, 2022)
Photoprotection by non-photochemical quenching is important for optimal growth and development, especially during dynamic changes of the light intensity. The main component responsible for energy dissipation is called qE. It has been proposed that qE involves the reorganization of the photosynthetic complexes and especially of Photosystem II. However, despite a number of studies, there are still contradictory results concerning the structural changes in PSII during qE induction. The main limitation in addressing this point is the very fast nature of the off switch of qE, since the illumination is usually performed in folio and the preparation of the thylakoids requires a dark period. To avoid qE relaxation during thylakoid isolation, in this work quenching was induced directly on isolated and functional thylakoids that were then solubilized in the light. The analysis of the quenched thylakoids in native gel showed only a small decrease in the large PSII supercomplexes (C 2 S 2 M 2 /C 2 S 2 M) which is most likely due to photoinhibition/light acclimation since it does not recover in the dark. This result indicates that qE rise is not accompanied by a structural disassembly of the PSII supercomplexes.

Molecular dynamics simulations in photosynthesis - Nicoletta Liguori; Roberta Croce; Siewert J. Marrink; Sebastian Thallmair (Photosynthesis Research, 2020)
Photosynthesis is regulated by a dynamic interplay between proteins, enzymes, pigments, lipids, and cofactors that takes place on a large spatio-temporal scale. Molecular dynamics (MD) simulations provide a powerful toolkit to investigate dynamical processes in (bio)molecular ensembles from the (sub)picosecond to the (sub)millisecond regime and from the Å to hundreds of nm length scale. Therefore, MD is well suited to address a variety of questions arising in the field of photosynthesis research. In this review, we provide an introduction to the basic concepts of MD simulations, at atomistic and coarse-grained level of resolution. Furthermore, we discuss applications of MD simulations to model photosynthetic systems of different sizes and complexity and their connection to experimental observables. Finally, we provide a brief glance on which methods provide opportunities to capture phenomena beyond the applicability of classical MD.

Carotenoid dark state to chlorophyll energy transfer in isolated light-harvesting complexes CP24 and CP29 - Daniel A. Gacek; Christoph-Peter Holleboom; Pen-Nan Liao; Marco Negretti; Roberta Croce; Peter Jomo Walla (Photosynthesis Research, 2020)

Time-resolved fluorescence measurements on leaves: principles and recent developments - Volha U. Chukhutsina; Alfred R. Holzwarth; Roberta Croce (Photosynthesis Research, 2019)

Introduction: light harvesting for photosynthesis - Anjali Pandit; Ivo H. M. van Stokkum; Herbert van Amerongen; Roberta Croce (Photosynthesis Research, 2018)

Light-harvesting complexes of Botryococcus braunii - Tomas E. van den Berg; Bart van Oort; Roberta Croce (Photosynthesis Research, 2018)

Invitation to the 17th international congress on photosynthesis research in 2016: photosynthesis in a changing world - Herbert van Amerongen; Roberta Croce (Photosynthesis Research, 2016)

Carotenoid–chlorophyll coupling and fluorescence quenching in aggregated minor PSII proteins CP24 and CP29 - Christoph-Peter Holleboom; Daniel Alexander Gacek; Pen-Nan Liao; Marco Negretti; Roberta Croce; Peter Jomo Walla (Photosynthesis Research, 2015)

Light-harvesting in photosystem I - Roberta Croce; Herbert van Amerongen (Photosynthesis Research, 2013)

Light harvesting in photosystem II - Herbert van Amerongen; Roberta Croce (Photosynthesis Research, 2013)

Ecotoxicity of pp’DDE to Daphnia magna - Roberta Bettinetti; Valeria Croce; Francesca Noè; Benedetta Ponti; Silvia Quadroni; Silvana Galassi (Ecotoxicology, 2013)

PMS: Photosystem I electron donor or fluorescence quencher - Emilie Wientjes; Roberta Croce (Photosynthesis Research, 2012)

pp´DDT and pp´DDE Accumulation in a Food Chain of Lake Maggiore (Northern Italy): Testing Steady-State Condition - Roberta Bettinetti; Valeria Croce; Silvana Galassi; Pietro Volta (Environmental Science and Pollution Research, 2006)

Absorption spectra of chlorophyll a and b in Lhcb protein environment - Gianfelice Cinque; Roberta Croce; Roberto Bassi (Photosynthesis Research, 2000)

The Soret absorption properties of carotenoids and chlorophylls in antenna complexes of higher plants - Roberta Croce; Gianfelice Cinque; Alfred R. Holzwarth; Roberto Bassi (Photosynthesis Research, 2000)

Model studies on the excited state equilibrium perturbation due to reaction centre trapping in Photosystem I - Robert C. Jennings; Giuseppe Zucchelli; Roberta Croce; Leonas Valkunas; Laura Finzi; Flavio M. Garlaschi (Photosynthesis Research, 1997)